Spatio-temporal patterns and prediction of colorectal cancer mortality in Chinese cancer registration areas: A nationwide study based on multiple models - Yu Zhao; Xiaoshuang He; Jianjiang Shao; Lei Zhu; Zhiqiang Chu; Yang Man; Jiageng He (PLoS ONE, 2026)
Objective To describe the spatiotemporal distribution characteristics of colorectal cancer (CRC) mortality in Chinese cancer registration areas and to predict its future trends, thereby providing an epidemiological basis for CRC prevention and control in China. Method This study used cancer registry data from 2005 to 2018, collected from the China Cancer Registry Annual Report (2008–2021), to comprehensively describe CRC mortality patterns. Joinpoint regression models were employed to calculate the annual percentage change (APC) and average annual percentage change (AAPC) to analyze temporal trends. The age–period–cohort model was used to disentangle the effects of age, period, and cohort. A Bayesian age–period–cohort (BAPC) model was constructed to predict future trends for 2019–2035. Global and local spatial autocorrelation methods were applied to describe the spatial distribution of CRC mortality and to identify high-risk areas. Results From 2005 to 2018, in Chinese cancer registration areas, the mortality of CRC was 14.45/100,000, and the age-standardized mortality rate (ASMR) was 11.13/100,000 [95% confidence interval (CI): 11.03, 11.27]. From 2005 to 2007, the mortality rate of CRC showed an upward trend, with an APC of 3.67% (95% CI: −0.77%, 8.33%); from 2007 to 2013, there was a significant downward trend with an APC of −2.45% (95%CI: −3.14%, −1.47%); from 2013 to 2018, there was an upward trend with an APC of 0.13% (95% CI: −0.88%, 1.17%). From 2007 to 2013, the CRC mortality rates of different genders showed a significant downward trend. In urban areas from 2009 to 2018, the CRC mortality rate showed a significant downward trend with an APC of −1.21% (95% CI: −1.71%, −0.71%), but in rural areas, it showed a significant upward trend with an AAPC of 0.59% (95% CI: 0.24%, 1.56%). The age effects indicated that the risk of CRC death increased with age. From 2019 to 2035, the ASMR of CRC in Chinese cancer registration areas will generally show a slow upward trend. Spatial autocorrelation analysis showed that the mortality rate of CRC in Chinese cancer registration areas exhibited spatial clustering characteristics, with hotspots concentrated in the eastern coastal and northeastern provinces. Conclusions The mortality rate of CRC in Chinese cancer registration areas showed a trend of first increasing, then decreasing, and then increasing from 2005 to 2018. It was predicted that it will continue to rise from 2019 and still face a series of challenges such as urban-rural, gender, and regional inequality. In the future, more targeted prevention and control strategies should be adopted, combined with dietary and lifestyle interventions, to further reduce the burden of CRC.